ISOL Eco-lexis in Indonesian children’s narratives: A mini-corpus study of frequency, range, and collocations - Nur Melansari; Khaerun Nisa’a Tayibu; Raviqa Raviqa; Madani Madani; Andi Muhammad Syafri Idris (Universitas Muhammadiyah Purwokerto, 2026)
Children’s stories are a powerful medium for introducing environmental awareness while simultaneously supporting literacy development. Yet, empirical descriptions of the environment-related vocabulary that children encounter in Indonesian narrative texts remain limited, particularly those drawn from openly accessible digital libraries. This study addresses that gap by conducting a corpus-based descriptive lexical analysis of eco-lexis in a mini-corpus of Indonesian children’s narratives sourced from Let’s Read (The Asia Foundation). The dataset comprises 10 narratives (N = 10; 4,886 cleaned tokens) spanning Reading Levels 1–5, selected using purposive stratified sampling with inclusion criteria of Indonesian language, narrative genre, environmental focus, and Creative Commons licensing (CC BY or CC BY-NC). The analysis integrates three complementary procedures: (1) lexical profiling through raw and normalized frequency (per 1,000 words), (2) distributional profiling using range (number of texts containing an item) as a pragmatic proxy for dispersion in a small corpus, and (3) phraseological analysis through recurrent bigrams/short phrases around key eco-lexis items. Eco-lexis identification combines a seed list with corpus-driven refinement and light manual lemmatization to group closely related variants. Results show that eco-lexis is organized around high-salience environmental entities (e.g., hutan, pohon, ikan, lumba-lumba, karang, udang, air, sungai, bakau), supported by recurring problem and action vocabulary that frames everyday stewardship (e.g., sampah, plastik, buang, bersih, jaga). Range patterns differentiate a compact core set (widely distributed across texts) from topic-bound clusters concentrated in one or two narratives (e.g., mangrove ecology and forest governance). Phrase-level patterns further reveal how narratives encode environmental responsibility through reusable “chunks,” including disposal routines (e.g. tempat sampah, membuang sampah) and protection frames (e.g. menjaga hutan, menjaga kelestarian). Overall, the study offers a transparent, lightweight workflow for eco-lexis profiling and provides an empirically grounded basis for selecting story texts and designing low-burden classroom tasks that link vocabulary development with environmental responsibility discourse.